Pengenalan Nilai-Nilai Budaya Lokal Masyarakat Tangerang Melalui Festival Cisadane - Rizki Abdillah Rachman; Andi Andi (CHRONOLOGIA, 2022)
This research is entitled "Introduction to the Local Cultural Values of the Tangerang Society through the Cisadane Festival". The background of the researcher choosing the title of this research is to introduce local cultural values that are packaged in a festival performance. This study also aims to determine the values contained in the Cisadane festival, the local government's efforts to improve local culture, and the role of the Cisadane festival in awakening the culture of the Tangerang people.The research method used is a qualitative method with a phenomenological approach. For data and data sources, researchers used 2 things, namely primary data and secondary data. The primary data is in the form of interviews with several informants and sources, while the secondary data is in the form of documentation studies such as through literature books, scientific works, national and international journals as well as mass media reports and electronic media.The result of this research is that the Cisadane festival has a variety of local elements in it, including Chinese, Sundanese, and Betawi ethnicities. The Tangerang city government in coordination with the culture and tourism department has made various efforts to improve regional culture, such as holding a festival every year and new innovations in it. This also shows that the Cisdane festival has a big role for the community, especially the city of Tangerang in instilling local cultural values.